Fenomenologia da imparcialidade: redução do outro ao mesmo ou abertura à alteridade? - Moor, Rudinei Cogo (2022)
The thesis starts from phenomenological conceptual contributions, and from its way of investigation, to think about impartiality. We defend that impartiality is a legitimate basis for opening up to alterity. The support of such thesis leads us to ask about the conditions and possibilities of an impartial experience. At first, we seek to describe subjectivity and its intentional functionalities in an impartial orientation, having as objective, the ideal of ethical life. In a second moment, in intersubjectivity, we will discern the irreducible strangeness of the other in responsive elaboration. The self-other relationship emerges as a support for thinking about the experience of impartiality and community life, but it can also be the basis of conflicts and duels. Therefore, there is a need for a third figure, capable of opening the dual relationship and serving as a guarantee of alterity. Impartiality is phenomenalized in the figure of the third. This is where the relationship between intentionality and responsiveness is based. As a third party of justice, comparison of uniqueness (faces) that implies responsibility. The impartial third appears not to show the self to itself, but to protect others from any appropriation. He comes as an echo that resounds as the original voice of the ethical relationship. As a testimony to the truth, the third appears as an ideal of ethical life that boosts the community to realize values, with a view to a just and authentic humanity. The impartiality is a function and duty of a third party. He who takes his place has the infinite task of being an functionary of humanity.